Improving Democratic Values in Civic Education Learning through Grouped-Discussion Method for the Students in Higher Education Institution - Priyanto, Eko (EDUCARE, 2014)
ABSTRACT: This study was aimed at improving the studentsâ democratic values among the students in higher education institution through a grouped-discussion method. This was trigerred by a lack of understanding on democratic values among the students in the uniersity level. They also indicated less-democratic attitudes and behavior. This was an action reseach study following the model of Stephen Kemmis & Robin McTaggart (1988). The subject of the research was the fourth-semester students at the Study Program of Indonesia and Local Languages Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto) in Central Java, Indonesia. There were 60 students. The action (treatment) given was an application of grouped-discussion in the Civic Education courses. The data collection was through observation from which the results was noted in an observation guide. In addition, it was also done through testing of essay questions and an interview. Two types of data were collected, i.e. qualitative data from document, results of observation, and recorded interview; and the quantitative data were from testing of pre- and post-test. Based on the analysis, it was proved that the democratic values among the students can be improved through grouped-discussion method applied in Civic Education course. Their average learning score was 63.75 before the treatment and it increased to 72.77 after the first cycle. At the end of the second cycle, it became 80.68. Besides, another increase was indicated from their democratic attitude and behavior. They acknowledged that every individual has a freedom of giving his/her opinion, of making a group of organization, and participating in any organization, appreciating citizen and gender equity, and respecting other peopleâs opinion. KEY WORDS: Democratic values, grouped-discussion, civic education, students, democratic attitude and behavior, and good citizen of Indonesia.About the Author: Eko Priyanto is a Lecturer at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto City, Central Java, Indonesia. E-mail: ahmadump@yahoo.co.idÂ How to cite this article? Priyanto, Eko. (2014). âImproving Democratic Values in Civic Education Learning through Grouped-Discussion Method for the Students in Higher Education Institutionâ in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.179-188. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December11, 2013); Revised (January 13, 2014); and Published (February17, 2014).Â Â